Analisis Pengaruh Variasi Produk, Desain Kemasan, Kebersihan, dan Lokasi terhadap Keputusan Pembelian Konsumen pada UMKM Tamaaman Cake - Fajriyah, Darari; Vindiana, Afina Putri; P.O, Annuridya Rosyidta; Tampubolon, Edward S. (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The increasing competition among micro, small, and medium enterprises (MSMEs) in the culinary sector has created a demand for businesses to better understand consumer purchasing behavior. This study aims to analyze the influence of product variation, packaging design, cleanliness, and store location on consumer purchasing decisions, specifically in the context of Tamaaman Cake, a cake and custom bakery based in Tangerang, Indonesia. A literature review approach was employed by systematically reviewing relevant national and international research articles published between 2020 and 2025. A total of ten empirical studies were selected using purposive sampling criteria, focusing on key variables related to consumer behavior in culinary MSMEs. The results show that all four factors product variation, packaging design, cleanliness, and store location play a significant role in shaping consumer purchasing decisions. Product variation provides consumers with flexibility to choose based on their preferences, while attractive and informative packaging enhances perceived product value. Cleanliness influences consumers’ trust and safety perception, and a strategic location increases ease of access, encouraging purchase intention. The findings emphasize the importance of a holistic marketing strategy that considers both tangible and intangible factors influencing consumer behavior. This study offers strategic insights for MSME practitioners, especially those in the food industry, to remain competitive by aligning their business attributes with evolving consumer expectations.